Global inequality: relatively lower, absolutely higher - Niño-Zarazúa, M; Roope, L; Tarp, F (Wiley, 2016)
This paper measures trends in global interpersonal inequality during 1975–2010 using data from the most recent version of the World Income Inequality Database (WIID). The picture that emerges using ‘absolute,’ and even ‘centrist’ measures of inequality, is very different from the results obtained using standard ‘relative’ inequality measures such as the Gini coefficient or Coefficient of Variation. Relative global inequality has declined substantially over the decades. In contrast, ‘absolute’ inequality, as captured by the Standard Deviation and Absolute Gini, has increased considerably and unabated. Like these ‘absolute’ measures, our ‘centrist’ inequality indicators, the Krtscha measure and an intermediate Gini, also register a pronounced increase in global inequality, albeit, in the case of the latter, with a decline during 2005 to 2010. A critical question posed by our findings is whether increased levels of inequality according to absolute and centrist measures are inevitable at today's per capita income levels. Our analysis suggests that it is not possible for absolute inequality to return to 1975 levels without further convergence in mean incomes among countries. Inequality, as captured by centrist measures such as the Krtscha, could return to 1975 levels, at today's domestic and global per capita income levels, but this would require quite dramatic structural reforms to reduce domestic inequality levels in most countries.